Peculiarities of the Adsorption of Heavy-Metal Ions from Aqueous Media by Modified Cellulose - Tatiana E. Nikiforova; Vladimir A. Kozlov; Vera A. Loginova (Adsorption Science & Technology)
Chemical modification of cotton cellulose with the formation of hydroxamic and aldehyde–bisulphite derivatives has been carried out. Sorption properties of initial and modified sorbents are investigated. It is established that a-hydroxycarboxyl groups, which are present in all three kinds of sorbents, form colourless chelate complexes due to the replacement of their protons with an equivalent amount of metal ions. Because of the charge transfer during metal–ligand interactions, coloured chelate complexes are formed. In the aldehyde–bisulphite groups, two singly charged ions (Na + and H + ) are consequently replaced with two equivalents of metal ion resulting in the formation of colourless chelate complexes. Sorption isotherms of metal ions by the samples of native and modified cellulose are well described by the Langmuir model. The maximum adsorption values and Henry's constants are in good agreement with the quantity and nature of cellulose acidic groups.